AUGMENTED REALITY AS A DISTANCE LEARNING TOOL UNDER QUARANTINE CONDITIONS - Viktoriia Tkachuk; Yuliia Yechkalo; Alla Taraduda; Iryna Steblivets ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The research paper describes methods of performing the laboratory work on studying the electro-measuring devices in the remote mode by using the mobile application Electricity AR.